Children From the Age of Three Show a Developmental Switch in T-Cell Differentiation - Knolle, Julienne; Pierau, Mandy; Hebel, Katrin; Lampe, Karen; Jorch, Gerhard; Kropf, Siegfried; Arens, Christoph; Brunner-Weinzierl, Monika C. (Frontiers in Immunology, 2020)
Every sixth child suffers from hypertrophy of the adenoid, a secondary lymphoid organ, at least once in childhood. Little is known about the impact of pathogen-provocation versus developmental impact on T-cell responses after 1 year of age. Therefore, developmental and infection-driven influences on the formation of T-cell-compartments and -multifunctionality in adenoids were analyzed taking into account patient’s history of age and inflammatory processes. Here, we show that in adenoids of 102 infants and children similar frequencies of naïve, effector, and memory T-cells were accumulated, whereby history of suffering from subsequent infection symptoms resulted in lower frequencies of CD4+ and CD8+ T-cells co-expressing several cytokines. While patients suffering from sole nasal obstruction had bal-anced Th1- and Th17-compartments, Th1 dominated in patients with concomitant upper air-way infections. In addition, analysis of cytokine co-expressing CD4+ and CD8+ T-cells showed that children at the age of three or older differed significantly from those being one- or two-years old, implicating a developmental switch in T-cell differentiation at that age. Yet, dissecting age and infectious history of the patients revealed that while CD8+ T-cell differentiation seems to be triggered by development, CD4+ T-cell functionality is partly impaired by infections. However, this functionality recovers by the age of three years. Thus, three years of age seems to be a critical period in an infant´s life to develop robust T-cell compartments of higher quality. These findings identify important areas for future research and distinguish an age period in early childhood when to consider adjusting the choice of treatment of infections.